1st Annual International Conference on Advanced Research: Physiology (ARP 2014) 2014
DOI: 10.5176/2382-607x_arp14.12
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid β-amyloid1–42 levels in the differential diagnosis of Alzheimer’s Disease – systematic review and meta-analysis

Abstract: The purpose of this study was to carry out systematic review of the literature and metaanalysis to evaluate the diagnostic utility of cerebrospinal fluid (CSF) levels of the 42 amino acid form of amyloid-beta (Aβ 1-42) as a biomarker for differentiating Alzheimer's disease (AD) from non-AD dementia. Methods Design. Systematic literature review was used to evaluate the effectiveness of the Aβ for the diagnosis of AD. The Scottish Intercollegiate Guidelines Network (SIGN) tool was used to evaluate independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Moreover, MgT treatment restored the CSF Aβ 1–42 levels in the APP/PS1 mice. These observations are in line with studies suggesting that reduced CSF Aβ 1–42 levels are a potential biomarker for the diagnosis of AD (35). We were interested to observe that the expression of APH‐1α/‐1 b was up‐regulated when we injected the CSF of APP/PS1 mice into WT mice intracerebroventricularly, and this up‐regulation was blocked by the addition of Aβ antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, MgT treatment restored the CSF Aβ 1–42 levels in the APP/PS1 mice. These observations are in line with studies suggesting that reduced CSF Aβ 1–42 levels are a potential biomarker for the diagnosis of AD (35). We were interested to observe that the expression of APH‐1α/‐1 b was up‐regulated when we injected the CSF of APP/PS1 mice into WT mice intracerebroventricularly, and this up‐regulation was blocked by the addition of Aβ antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…Further to preanalytical factors, concentrations of CSF Aβ also vary between individuals [33]; thus, individuals with constitutively high or low quantities of Aβ 42 relative to chosen diagnostic “cut points” may be vulnerable to misinterpretation of test results. Recent meta‐analysis shows that when comparing AD versus nondemented controls and non‐AD dementias, CSF Aβ 42 has a pooled sensitivity of 0.80 (95% confidence interval = 0.78–0.82) and a pooled specificity of 0.76 (95% confidence interval = 0.74–0.78) [34]. Increasingly, reports suggest improved diagnostic and mild cognitive impairment–AD conversion predictive power when Aβ 42 is considered in ratio to Aβ 40 [1,15,16,31,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found a significant effect of tau pathology on the Aβ1-42/Aβ1-40 ratio in the culture medium, with samples containing tangles showing the highest Aβ1-42/Aβ1-40 ratio. More commonly conducted studies examining CSF from human patients have observed an overall decline in Aβ1-42 and Aβ1-42/Aβ1-40 ratio during normal ageing, which is exacerbated by both APOE4 genotype and a diagnosis of AD [16][17][18][19]26,28,85 . Again, the lack of change in Aβ1-42 over time in our sample set differs from this, which may reflect different processes being captured in HBSC medium versus CSF/ISF, or could be due to limits in ELISA sensitivity for Aβ1-42.…”
Section: Discussionmentioning
confidence: 99%